ANALYSIS OF THE COMMUNITY-BASED TOTAL SANITATION PROGRAM IMPLEMENTATION IN SOPPENG DISTRICT - Dian Meiliani Yulis; Andi Agustang; Nurlita Pertiwi; Syamfitriani Asnur (International Conference on Social and Islamic Studies, 2021)
Indonesia still has considerable health development challenges, notably in the areas of hygiene and sanitation. As a result, a comprehensive sanitation strategy is required. The government altered its national sanitation development strategy from sectoral concentration to hardware subsidies, which have failed to influence hygienic behavior and access to sanitation. This evolved into a community-based sanitation system that stressed five (five) factors, including the elimination of open defecation, proper management of drinking water and household food, hand washing with soap, proper waste management, and safe domestic liquid waste management. The purpose of this study was to ascertain the effect of predisposing factors, which included elements of knowledge, attitudes, and perceptions, on the five STBM pillars. To determine the effect of STBM triggering, a quantitative observational design using a cross sectional study technique was adopted. The findings indicated that knowledge, attitudes, family support, and assistance from health care professionals were all strongly associated with STBM application. Meanwhile, statistical analyses indicate that the number of dependents, employment status, income, and water availability are unrelated to the application of STBM. With a significant value (sig.=0.000) or p<0.010 and Exp(B)=12,267, knowledge is the most influential variable on STBM implementation. As a conclusion, respondents' knowledge of the implementation of STBM is the most influential factor in the implementation of STBM. It is hoped that all parties, particularly family members and health staff, would encourage and help one another, motivating the community to constantly preserve sanitation in their surroundings.